2022
DOI: 10.3390/nano12101747
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility Interpretation and MHD Mixed Convection of Hybrid Nanofluids in a 3D Heated Lid-Driven Chamber

Abstract: This paper presents a numerical simulation of a magneto-convection flow in a 3D chamber. The room has a very specific permeability and a zigzag bottom wall. The fluid used in this study is Al2O3-Cu/water with 4% nanoparticles. The Galerkin finite element technique (GFEM) was developed to solve the main partial equations. The hybrid nanofluid inside the container is subjected to the horizontal motion of the upper wall, an external magnetic field, and a thermal buoyancy force. The present numerical methodology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The findings indicated that the HNF's rate of energy transmission is significantly higher than that of the nanoliquid. Houssem et al 20 and Puneeth et al 21 described the flow of HNF and gyrotactic microorganisms subject to the characteristics of Casson nanofluid. Sohut et al 22 testified the water-based copper-alumina HNF in a tilted cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that the HNF's rate of energy transmission is significantly higher than that of the nanoliquid. Houssem et al 20 and Puneeth et al 21 described the flow of HNF and gyrotactic microorganisms subject to the characteristics of Casson nanofluid. Sohut et al 22 testified the water-based copper-alumina HNF in a tilted cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been a significant number of researches aimed at studying the heat transfer within thermal exchangers (Mokeddem et al 2019;Alam and Kim 2018;Shirvan et al 2016;Laidoudi and Bouzit 2017a;Nguyen and Ahn 2021). The papers can be classified into two main groups: the first group is concerned with studying the geometry of the heat exchanger (Zimparov 2001;Laidoudi and Bouzit 2018;Kukulka et al 2011;Fan et al 2009;He et al 2019), while the second aims to examine the effect of the fluid quality (Aliouane et al 2021;Aissa et al 2022a;Aissa et al 2022b;Laidoudi et al 2022;Laidoudi and Ameur 2022b). Previous work has been achieved either through real experimental (Peyghambarzadeh et al 2011;Liu et al 2006;Bouvier et al 2003) or through numerical simulations (Laidoudi 2020a;Herouz et al 2023;Mohammed et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two proven methods include enhancing free convection heat transmission inside the cavity by adding nanoparticles to the fluid and producing turbulence flow. Because of the fluid’s altered viscosity and thermal conductivity, the presence of nanoparticles in the fluid causes an abnormal treatment of nanofluids [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%